Characterization of a Parkinson's disease rat model using an upgraded paraquat exposure paradigm. (3rd February 2020) - Cristóvão, Ana Clara; Campos, Filipa L.; Je, Goun; Esteves, Marta; Guhathakurta, Subhrangshu; Yang, Lichuan; Beal, M. Flint; Fonseca, Beatriz M.; Salgado, Antonio J.; Queiroz, João; Sousa, Nuno; Bernardino, Liliana; et al.
Abstract: Animal models of human diseases are crucial experimental tools to investigate the mechanisms involved in disease pathogenesis and to develop new therapies. In spite of the numerous animal models currently available that reproduce several neuropathological features of Parkinson disease (PD), it is challenging to have one that consistently recapitulates human PD conditions in both motor behaviors and biochemical pathological outcomes. Given that, we have implemented a new paradigm to expose rats to a chronic low dose of paraquat (PQ), using osmotic minipumps and characterized the developed pathologic features over time. The PQ exposure paradigm used lead to a rodent model of PD depicting progressive nigrostriatal dopaminergic neurodegeneration, characterized by a 41% significant loss of dopaminergic neuron in the substantia nigra pars compacta (SNpc), a significant decrease of 18% and 40% of dopamine levels in striatum at week 5 and 8, respectively, and a significant 1.5‐fold decrease in motor performance. We observed a significant increase of microglia activation state, sustained levels of α‐synucleinopathy and increased oxidative stress markers in the SNpc. In summary, this is an explorative study that allowed to characterize an improved PQ‐based rat model that recapitulates cardinal features of PD and may represent an attractive tool to investigate several mechanisms underlying the various aspects of PD pathogenesis as well as for the validation of the efficacy of new therapeutic approaches that targets different mechanisms involved in PD neurodegeneration. Abstract : Improved PQ‐based rat model recapitulates cardinal features of PD pathology. The new low dose of PQ exposure paradigm using osmotic minipumps, generated a rodent model of PD that reproduces increases of the nigrostriatal dopaminergic lesion, sustained neuroinflammation, oxidative stress and α‐synuclein pathology overtime, complemented with the motor deficit.